Impacts of using EGR and different DI-fuels on RCCI engine emissions, performance, and combustion characteristics. (August 2022) - Elkelawy, Medhat; El Shenawy, E.A.; Mohamed, Sherif A.; Elarabi, Mostafa M.; Bastawissi, Hagar Alm-Eldin
Highlights: EGR contributed to further reductions in NOx emissions in RCCI combustion. Improvements in BTE and BSFC were achieved by using EGR in RCCI combustion. Better RCCI operation with EGR requires an alternating premixed fraction. Increased biodiesel dose in DI-Fuel lead to an increment in NOx emissions. Abstract: Exhaust gas recirculation (EGR) seems to be a critical parameter in developed RCCI operations for controlling emissions, in-cylinder charge reactivity as well as combustion phasing. The most advantages of utilizing the RCCI burning technique are the simultaneous decrease of PM as well as NOx emissions. Nevertheless, significant challenges remain, such as extreme HC and CO emissions. The purpose of this work is to investigate the effects of external, hot, and high-pressure EGR as well as different DI-Fuels on RCCI combustion under various load conditions. The tests were performed on direct injection, single-cylinder, and four-stroke modified diesel engine (peak power 5 KW under 1500 rpm) operating in RCCI mode with an EGR system. To initiate ignition, high reactivity fuel (biodiesel/diesel blends) was injected directly inside the engine's cylinder whereas low reactivity fuel (LPG) was induced into to intake mixing chamber. EGR at various ratios (30%, 20%, and 10%) was introduced into the engine via the intake mixing chamber, and experiments were done under various loads. The results show that increasing EGR results in a slight increment in BTE under medium and high engine loads. NOx emissions from diesel engines operating in traditional RCCI mode declined dramatically, and they decreased even further with the addition of EGR. The CO and HC emission levels, on the other hand, are slightly greater when EGR is used. Increasing the proportion of biodiesel in DI-Fuel is resulting in a decrement in BTE and NOx emissions in addition to an increment in BSFC, CO, and HC emissions.